PEMANFAATAN FERMENTASI LIMBAH CAIR TAHU TERHADAP PERTUMBUHAN SELADA MERAH (Lactuca sativa L var. Red) DENGAN TEKNIK HIDROPONIK SISTEM RAKIT APUNG - Imam Mahadi; Nursal Nursal; Desta Manulang; Bakhendri Solfan (Jurnal Agroteknologi, 2023)
The use of tofu waste water using the hydroponic technique of the floating raft system is not well known, so it needs to be done as an innovation. The purpose of this research was to determine the effect of tofu liquid waste fermentation on the growth of red lettuce (Lactuca sativa L var. Red rapids) using the floating raft hydroponic technique. The research was carried out in an experimental stage, namely the effect of tofu liquid waste on the growth of red lettuce (Lactuca sativa L var. Red rapids). This research method is an experimental method using a completely randomized design (CRD) consisting of 5 treatments and 3 replications. Parameters observed were plant height, leaf width, number of leaves, root length, wet weight and dry weight. The results of the analysis of variance (Anava) at 5% level, the use of tofu liquid waste showed a significant effect on the growth of red lettuce. Giving a concentration of 2.5 liters of tofu liquid waste with 5 liters of water resulted in the best growth of red lettuce.